Association between polymorphisms of adenosine A2A receptor gene and polymorphisms of ATP P2X7 receptor gene and the severity of SARS-CoV-2 infection - Lindo, Jorge Varandas (2022)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina